A linguagem das trevas na filosofia de Hobbes - Vander Schulz Nothling de Paula (2011)
In the fourth part of Leviathan, Hobbes denounces the fraud established by certain religious groups which make use of language to promote their own power over men and discusses their main doctrines, by pointing out not only their foundations, but also the risks they represent to the political stability of the Commonwealth. In this work, we intend to examine some of those doctrines and demonstrate that each one of them may be understood as an abuse of language.